2005
DOI: 10.1080/09583150500136873
|View full text |Cite
|
Sign up to set email alerts
|

Oil emulsions increase efficacy ofPhoma herbarumto control dandelion but are phytotoxic

Abstract: Paraffinic-vegetable and vegetable oil emulsions were investigated for their ability to increase efficacy of the fungal pathogen Phoma herbarum as a bioherbicide to control dandelion (Taraxacum officinale ) under sub-optimal leaf wetness durations (LWDs) in controlled environments. Mycelia of P. herbarum (20%, v/v) were formulated in 10 oil emulsions; two based on paraffinic-vegetable (soybean) oil mixtures, and eight based on vegetable (canola, coconut and soybean) oil emulsions alone. Emulsions were applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Three species within the genus Phoma have also received attention as potential agents for biological weed control (Table 1 ). P. herbarum , a fungal pathogen originally isolated from dandelion leaf lesions in Southern Ontario, has been investigated for control of dandelions in turf ( Neumann and Boland, 1999 ; Stewart-Wade and Boland, 2005 ). P. macrostoma has also been investigated for similar purposes as it has been observed to specifically inhibit the growth of dicot plants ( Bailey et al, 2011 , 2013 ; Smith et al, 2015 ).…”
Section: Biological Control Of Weeds Using Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Three species within the genus Phoma have also received attention as potential agents for biological weed control (Table 1 ). P. herbarum , a fungal pathogen originally isolated from dandelion leaf lesions in Southern Ontario, has been investigated for control of dandelions in turf ( Neumann and Boland, 1999 ; Stewart-Wade and Boland, 2005 ). P. macrostoma has also been investigated for similar purposes as it has been observed to specifically inhibit the growth of dicot plants ( Bailey et al, 2011 , 2013 ; Smith et al, 2015 ).…”
Section: Biological Control Of Weeds Using Fungimentioning
confidence: 99%
“…The research pipeline from the screening stage to field conditions faces a number of unique challenges (Figure 1 ). One commonly reported challenge is the need for continuous moisture availability during the period in which the biocontrol agent infects the plant ( Auld et al, 1990 ; Schisler et al, 1991 ; Auld and Morin, 1995 ; Stewart-Wade and Boland, 2005 ; Boyette and Hoagland, 2015 ). In a review of bioherbicide technology published by Auld and Morin (1995) , it was reported that dew periods of more than 12 hours are commonly necessary for bioherbicide candidates to successfully infect their hosts.…”
Section: Real World Factors That Affect the Efficacy Of Bioherbicidesmentioning
confidence: 99%
“…The majority of the studies were on soybean oil, reportedly less phytotoxic than petroleum‐based or mineral oils 15, 16, 22. The acute phytotoxicity observed on cherry leaves has also been reported for soybean oil applications on apple,17 dandelion15 and grape;16 in most cases, damage increased with increasing concentration. When applied directly to soybean leaflets, propylene glycol was not phytotoxic at concentrations up to 10%,21 yet did cause chlorosis and necrosis on soybean and corn leaves when introduced in vapour form in a controlled chamber 20…”
Section: Discussionmentioning
confidence: 97%
“…Of the ingredients known to be in the bait matrix, soybean oil and propylene glycol have been previously investigated for potential phytotoxicity on a variety of crops,14–21 although other ingredients, such as ammonium acetate, have not been ruled out as potential contributing factors. The majority of the studies were on soybean oil, reportedly less phytotoxic than petroleum‐based or mineral oils 15, 16, 22. The acute phytotoxicity observed on cherry leaves has also been reported for soybean oil applications on apple,17 dandelion15 and grape;16 in most cases, damage increased with increasing concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Within the genus Phoma, three species have a potential against weed control. P. herbarum is a fungus that is isolated from lesions of dandelion leaf that have shown control effects of dandelion [135]. P. macrostoma has also been studied for weed control due to its inhibitory effects on the dicot plants [18,136,137].…”
Section: Fungi (Mycoherbicides) In Biological Weed Controlmentioning
confidence: 99%